A qualitative study of the Scottish homeless service provisions through the production of reflexive mapping exercises. (November 2021) - Dickson, Kirsty; Rodriguez, Andrea; Freeman, Ruth; Gupta, Ekta; Walkden, Clare
Abstract: Background: The Scottish oral health and psychosocial wellbeing programme, Smile4life, identified a scarce knowledge of the health and social services available for those going through homelessness or at risk of becoming homeless. The Public Bodies (Joint Working) (Scotland) Act 2014 aims to integrate health and social care in Scotland to meet the needs of vulnerable populations. The Reflexive Mapping Exercise aims to integrate care by providing a framework to map services that allows for analysis of the geographic distribution and types of support that has been offered. The reflexive component discusses joint strategies to integrate services, improve practices, and reduce unequal distribution that might marginalise individuals, limiting their access and engagement with services. Methods: The reflexive mapping framework aims to maximise participation and development through co-designed participatory research, involving an advisory group composed of key stakeholders and individuals with lived experience. Policy makers and practitioners working in the homelessness sector collaborated to gather, review, and update the data collected about services through online searches, telephone calls, institutional visits, and event consultations. An analysis of the current service provision was made to identify deficits and areas to improve. Findings: The mapping is a visual and descriptive publication that includes services from different areas of support and their referral pathways. The completed mappings and reflexive exercises have shown a scarcity of services allocated to the most deprived areas of Scotland, with the majority of services seeking to address crisis periods with little aim at prevention, early intervention, and sustainability. Interpretation: The mapping process identified the need to take a prophylactic approach and create a more equitable distribution of services. The Reflexive Mapping Exercise helps to provide a framework that promotes communication and integration of health and social care services among practitioners and vulnerable services users. A reflexive approach helps to plan the strategic delivery of homeless services in Scotland with the service user at the forefront of care. The limitations surrounding the dynamic nature of service provision changes have been identified and are planned to be addressed through the formation of an online interactive resource. Funding: This work was supported by Scottish Government (grant number 121.80.4497).